(untitled) (Research, Society and Development, 2021)
Nematodes can cause annual losses in the order of 100 billion dollars in crops worldwide. Its control using chemical nematicides proves to be quite aggressive to the environment. For this reason, the management of microorganisms has been promising. However, it is essential to know the control potential of each organism. Thus, the objective of this study was to verify the efficiency of different microorganisms in the biological control of Meloidogyne sp. A systematic review of the literature was carried out from 2000 to 2020 with the keywords “Meloidogyne and biology control", resulting in 659 articles, of which 51 were pre-selected and, after the more detailed evaluation, was selected ten published articles. These ten articles generated a total of 83 studies for meta-analyses. Each study included a treatment group using some microorganisms (bacteria, fungus, actinomycetes) for nematode biocontrol, a control group without using biocontrol agents. From this meta-analysis, we can observe that the use of microorganisms decreased the number of galls (42.05%), the number of eggs (57.77%), the gall index (28.58%) and the eggs mass (53.48%). The use of microorganisms was also positive in increasing root mass (832.89%). We can conclude that the use of microorganisms proved to be efficient in controlling nematodes M. javanica and M. incognita. The fungi Pleurotus ostreatus and Phanerochaete chrysosporium have more significant potential for biocontrol for these species.